System Review of Effect of Shadowboxing Exercise on Sleep Quality of the Elderly - Maomao HUANG; Weiqiang MU; Guohua ZHENG (康复学报)
Objective:To evaluate the effect of shadowboxing exercise on sleep quality of the elderly for providing reliable evidence for clinical application.Methods:The inclusion criteria, exclusion criteria and retrieval strategies of original literatures were established, and then randomized controlled trials (RCTs) and non-randomized controlled trials (NRCT) related to the effect of shadowboxing exercise on sleep quality of the elderly were collected. According to bias risk assessment tool of Cochrane, the quality of the studies was evaluated and the related information was extracted, ReMan 5.2 software was used for meta-analysis and statistical appraisal of effect size.Results:six RCTs and one NRCT with a total of 673 participants were brought into the investigation. Results of meta analysis showed that compared with blank control group, the score of sleep quality in pittshurgh sleep quality index (PSQI) in shadowboxing exercise group was decreased [SMD-0.85, 95%CI (-1.25, -0.45), P<0.000 1], the score of sleep latency was decreased [SMD-1.31, 95%CI (-1.57, -1.05), P<0.000 01], the score of sleep disturbance was decreased [MD-0.36, 95%CI (-0.53, -0.20), P<0.000 1], the score of sleeping medications was decreased [MD-0.29, 95%CI (-0.45, -0.13), P=0.000 3], the score of daytime dysfunction was decreased [MD-0.19, 95%CI (-0.30, -0.08), P=0.000 7], and the total score of PSQI was decreased [MD-2.12, 95%CI (-3.00, -1.24), P<0.000 01].Conclusion:Shadowboxing exercise can improve sleep quality ofthe elderly, but whether the curative effect is long-term would still need more high-quality RCTs to confirm.